2013
DOI: 10.1016/j.soscij.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Concern about the rise of lazy welfare queens? An empirical explanation of the underdevelopment of the redistributive welfare system in South Korea

Abstract: a b s t r a c tThis study investigates why South Korea has maintained a minimalist welfare state with little redistribution of income. Inspired by the behavioral/attitudinal approach of Alesina and his colleagues, this study focuses on the perception that people who do not work become lazy. This belief is related to the anti-welfare sentiment that non-working benefits encourage laziness. This study shows that perceptions of work and laziness are associated with preferences for redistribution, not only among So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Some argue that welfare chauvinist ideas are generally associated with insurance‐based, contributory welfare states (Ennser‐Jedenastik, 2018), while others have found that universal provision is associated with lower levels of such attitudes (Mau & Burkhardt, 2009). Our results indicate that respondents favour welfare for those who work and are thus ‘contributing’, as other scholarship on South Korean welfare attitudes has found (Roh, 2013), but nonetheless a strong preference for those with low incomes – that is support for means testing. Paradoxically, however, when given the chance to impose recipient contribution requirements (rent co‐payment), we find little evidence of an origins‐based discrimination effect.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some argue that welfare chauvinist ideas are generally associated with insurance‐based, contributory welfare states (Ennser‐Jedenastik, 2018), while others have found that universal provision is associated with lower levels of such attitudes (Mau & Burkhardt, 2009). Our results indicate that respondents favour welfare for those who work and are thus ‘contributing’, as other scholarship on South Korean welfare attitudes has found (Roh, 2013), but nonetheless a strong preference for those with low incomes – that is support for means testing. Paradoxically, however, when given the chance to impose recipient contribution requirements (rent co‐payment), we find little evidence of an origins‐based discrimination effect.…”
Section: Introductionsupporting
confidence: 78%
“…Second, attitudes with respect to welfare deservingness also appear to have a significant impact on allocation decisions. Existing research has shown that South Koreans believe poverty results from ‘laziness’ and that the idle are not worthy of public assistance (Roh, 2013). Our findings also indicate that respondents clearly favour welfare for the working over those who do not, and this also suggests that South Korea's contribution‐based system of welfare reflects popular preferences, as Roh (2013) has argued.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In Korea, although unions were involved in the Tripartite Commission, their power should not be exaggerated as they are comparatively unorganized. This is well indicated by the union density rate of about 10 percent when the country was hit by the crisis in 1997 (Roh, 2013;Visser, 2011). In Italy, union power to participate in the reform process has disappeared, when comparing its relations with the government in the 1992 and 2012 crises (Culpepper and Regan, 2014;Sacchi, 2013).…”
Section: Conclusion: Conditionality and The Role Of Domestic Factorsmentioning
confidence: 83%
“…In August 1999, the Korean government declared a new guiding principle for social protection. It emphasized social safety nets as citizenship rights (Office of the President of Korea, 2000), which was a considerable change in Korea, where the growth-first-redistribution-later ideology had prevailed for more than 30 years (Ramesh, 1995;Roh, 2013).…”
Section: The Expansion Of Welfare Spending and Policy Change In Koreamentioning
confidence: 99%